2009
DOI: 10.1007/s12665-009-0263-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of groundwater environment of Kathmandu Valley

Abstract: Kathmandu Valley aquifer in central Nepal is continuously under stress since the commencement of mechanized extraction of groundwater resources in early 1970s. Many wells have been drilled in shallow and deep aquifers of the valley; and numerous studies have been made in last four decades to understand the aquifers. However, up-to-date information on well inventory, water extraction, water quality and overall situation of groundwater environment are not yet known in the absence of institutional responsibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 6 publications
1
56
0
Order By: Relevance
“…Inequitable distribution of water across ward number 28 is also evident which has forced over extraction of ground water. It is found that anthropogenic factors such as over-exploitation of ground water are major drivers that exert pressures on groundwater environment which has lowered the groundwater levels and raised concerns on risks of land subsidence in area with high compressible clay and silt layers (Pandey et al, 2010).…”
Section: Ground Wateravailability and Usementioning
confidence: 99%
“…Inequitable distribution of water across ward number 28 is also evident which has forced over extraction of ground water. It is found that anthropogenic factors such as over-exploitation of ground water are major drivers that exert pressures on groundwater environment which has lowered the groundwater levels and raised concerns on risks of land subsidence in area with high compressible clay and silt layers (Pandey et al, 2010).…”
Section: Ground Wateravailability and Usementioning
confidence: 99%
“…The mineral composition of the aquifer material is dominated by quartz, K-feldspar, plagioclase, and mica with minor chlorite and calcite (Paudel et al 2004). The groundwater basin is home to 1.53 million people (population density is 4,690 person/km 2 ), 84.3 % of them live in urban areas (Pandey et al 2010). Groundwater is a major source of domestic water supply for those populations.…”
Section: Study Areamentioning
confidence: 99%
“…Groundwater extraction has been continuously increasing since the 1970s, with extraction exceeding recharge since the mid-1980s. This is mainly due to increase in population density from 3,150 to 4,690 persons/ km 2 during 1991-2001 (Pandey et al 2010). With no regulations on groundwater use and no management interventions, current status of achievements in sustainable groundwater management is relatively 'poor' .…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations